JAXA-ONERA-DLR cooperation: Results from rotor optimization in hover - Wilke, G.; Baily, J.; Kimura, K.; Tanabe, Y. (My University, 2021)
A cooperation on the aerodynamic optimization of helicopter rotors has been formed by JAXA, ONERA and DLR. This work represents the conclusions drawn from the first phase: optimization of a hovering rotor. The HART-II blade is first investigated with low-fidelity tools and compared against state-of-the art CFD simulations. Following up on this, the HART-II blade chord distribution and twist are optimized with the low-fidelity tools as well as CFD. Due to observed differences in the outcome of the CFD simulations for the low-fidelity optimized blades by the partners, a deeper investigation of the effects of the turbulence modelling approach, elasticity and grid topology is undertaken. The outcome is that the chosen flight condition is close to thrust of the maximum Figure of Merit and the vortex triggered separation on the outboard sections of the blade has to be modelled correctly. In this study, the blade grids had the most noticeable effect on the results, followed by the turbulence model and elasticity. With respect to the optimization, care must be taken when optimizing with low-fidelity methods, whereas CFD optimized blades were found to lead to more robust designs even though they have only been optimized for a single point. Reason is the more accurate modelling of the stall phenomenon with respect to geometrical changes.